Courtly love undressed : reading through clothes in medieval French culture - Burns, E. Jane, 1948- (Middle Ages series., 2002)
In the later Middle Ages clothing was used to mark religious, military, and chivalric orders; in the courtly milieu, more specifically, the ostentatious display of luxury dress was used as a means of self-definition for the ruling elite. In Courtly Love Undressed, E. Jane Burns explores the representation of this material culture in the literary texts and other documents that imagine various functions for elite clothing in twelfth- and thirteenth-century France.